Phonon effects in deep-level spectra of metals Beyond the linear-screening and linear-coupling models (1997)
ABSTRACT: Using a variational procedure within the effective-mass approximation we calculate the binding and transition energies of shallow-donor impurities in cylindrical pills of GaAs low-dimensional systems, under the action of an electric field applied in the axial direction, and considering an infinite confinement potential. We calculate the binding and transition energies as a function of the system geometry, the applied electric field, and the donor-impurity position. We have found that the presence of the electric field breaks the axial symmetry for the binding energy of the ground and excited states of the impurity and together with the impurity position, the geometric confinement is determinant for the existence of bounded excited states in these structures. In the two-dimensional limit and with low electric fields we obtained the expected four effective Rydbergs for the binding energy of the 1s-like state. In addition, and only for high electric fields, we obtained the reverse transitions.